1999
DOI: 10.2466/pms.1999.89.3f.1133
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Magnitude Estimation Scaling of Rock Music by Children, Young Adults, and Older People

Abstract: The present study concerned the perceptual processing of complex auditory stimuli in 10 children (M age = 8.1) as compared to 10 young adults (M age = 19.3) and 10 older adult subjects (M age = 54.2). The auditory stimulus used was 10 sec. of rock music (Led Zeppelin, 1969). All three groups provided numerical responses to nine intensities of the rock music stimulus (10, 20, 30, 40, 50, 60, 70, 80, 90 dB above threshold). Analysis showed that the children reported a wider range of numerical responses than both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In an interesting and well-designed study on the perception of complex sound in schizophrenia and mania [19]; complex nonverbal sounds with 3 s duration were used. They were used instead of music as they are more simple to analyze.…”
Section: Reviewmentioning
confidence: 99%
“…In an interesting and well-designed study on the perception of complex sound in schizophrenia and mania [19]; complex nonverbal sounds with 3 s duration were used. They were used instead of music as they are more simple to analyze.…”
Section: Reviewmentioning
confidence: 99%
“…Although there have been extensive psychological studies which investigated that there can be systematic interference or effectiveness in the discrimination tasks (Bundesen, 1990;Duncan et al, 1999;Larsen et al, 2003), comparatively few human behavioral studies have revealed correlations between human performance and concurrent modalities in magnitude estimation tasks (Stein et al, 1996). Most of studies in the magnitude estimation tasks have focused on how the individual differences of gender, age, or preference make change on the rating performance of single-modality stimulus (Banks et al, 1994;Ellis, 1999;Fucci and Petrosino,1997;Fucci et al, 1999).…”
Section: Introductionmentioning
confidence: 99%